Clinical benefits and recovery of delayed-type hypersensitivity in patients with AIDS-related complex treated with IMREG-1 or placebo - Fiala, M; Cone, L A; Sayre, J W (International journal of immunopharmacology, 1991)
IMREG-1, an immunomodulatory biological therapeutic, was studied in a placebo-controlled, double-blind, six-month trial in 45 anergic patients with AIDS-related complex (ARC) and 4 with Kaposi's sarcoma, which was followed by compassionate IMREG-1 administration to all subjects. The IMREG-1 group had significantly less AIDS-defining events compared with the placebo group during the randomized trial (6.9 events per 100 person-years vs 43.7 events per 100 person-years, P = 0.018, relative risk 6.33) and the total observation period. Patients receiving IMREG-1 significantly improved their work performance. Nine (41%) of 22 patients in the IMREG-1 group, compared with one (14%) of seven in the placebo group, recovered cutaneous reactivity to tetanus toxoid. At the end of the six-month trial, CD4+ counts were 0.429 x 10(9)/l in the IMREG-1 group and 0.304 x 10(9)/l in the placebo group (P = 0.04). IMREG-1 is a promising therapeutic for HIV-infected patients with symptoms of ARC.